Correction to: Transverse oscillations and an energy source in a strongly magnetized sunspot (Nature Astronomy, (2023), 7, 7, (856-866), 10.1038/s41550-023-01973-3) - Yuan D.; Fu L.; Cao W.; Kuźma B.; Geeraerts M.; Trelles Arjona J.C.; Murawski K.; Van Doorsselaere T.; Srivastava A.K.; Miao Y.; Feng S.; Feng X.; Noda C.Q.; Cobo B.R.; Su J. (My University, 2025)
Correction to: Nature Astronomyhttps://doi.org/10.1038/s41550-023-01973-3, published online 25 May 2023. In the version of the article initially published, in the third paragraph of the “Energy flux of the fibril oscillations” section, the text now reading “densities were 6.33 × 10−10 kg m−3 and 3.72 × 10−10 kg m−3” previously read “densities were 6.33 × 10−4 kg m−3 and 3.72 × 10−4 kg m−3”. This has been amended in the HTML and PDF versions of the article. © The Author(s) 2024.